Implementation of RSA Cryptosystem for Next Generation RFID Tags - Dighe, Ashish Arun (Université d'Ottawa / University of Ottawa, 2011)
This thesis addresses concepts of implementing a RSA cryptosystem on a passive RFID tag. With a limited number of public key cryptosystems on passive RFID platforms, the proposed algorithm makes use of Montgomery multiplication primitives to reduce the amount of computation required on the power constrained tag therefore making the proposition viable. Public key cryptography is being suggested for next generation RFID systems to reduce the number of possible attack vectors native to this type of technology. By estimating the area, power and time constraints of the RFID platform, it was determined that the area constraint was the critical variable in determining the maximum implementable security variable. Although the application of this algorithm has been targeted for passive HF RFID platforms, the algorithm could be used in other low power, sized constrained applications.
Keywords: RFID; Montgomery Multiplication; RSA